Environmental and Health Impacts of Air Pollution: A Review - Manisalidis, Ioannis; Stavropoulou, Elisavet; Stavropoulos, Agathangelos; Bezirtzoglou, Eugenia (Frontiers in Public Health, 2020)
One of our era’s greatest scourges is air pollution, not only for its impact on climate change but also for its impact on public and individual health by increasing morbidity and mortality. There are many pollutants consisting a major factor of disease in humans. Among them, Particulate Matter(PM), particles of variable but very small diameter, pen-etrate the respiratory system via inhalation, causing respiratory and cardiovascular dis-eases, reproductive and central nervous system dysfunctions as well as cancer. Despite the fact that ozone in the stratosphere plays a protective role in ultraviolet irradiation, it is harmful when in high concentration on ground-level, also affecting the respiratory and cardiovascular system. Furthermore, nitrogen oxide, Sulphur dioxide, Volatile Organic Compounds (VOCs), dioxins and polycyclic aromatic hydrocarbons (PAHs), all are considered as air pollutants harmful to the human. Carbon monoxide can even provoke direct poisoning when breathing in it at high levels. Heavy metals such as lead, when absorbed from the human body can lead to direct poisoning or chronic intoxication depending on exposure. Diseases occurring from the aforementioned substances include principally respiratory problems such as Chronic Obstructive Pulmonary Disease (COPD), asthma, bronchiolitis, lung cancer, cardiovascular events, central nervous system dysfunctions and cutaneous diseases. Last but not least, climate change, resulting from environmental pollution affects the geographical distribution of many infectious diseases as do natural disasters. The only way to tackle with the problem is Public awareness coupled with a multidisciplinary approach of scientific experts; national and international organizations must address the emergence of this flail and propose sustainable solutions.